Fluorophores for live cell imaging of AGT fusion proteins across the visible spectrum. (August 2006) - Keppler, Antje; Arrivoli, Claudio; Sironi, Lucia; Ellenberg, Jan
O 6 -alkylguanine-DNA alkyltransferase (AGT) fusion proteins can be specifically and covalently labeled with fluorescent O 6 -benzylguanine (O 6 -BG) derivatives for multicolor live cell imaging approaches. Here, we characterize several new BG fluorophores suitable for in vivo AGT labeling that display fluorescence emission maxima covering the visible spectrum from 472 to 673 nm, thereby extending the spectral limits set by fluorescent proteins. We show that the photostability of the cell-permeable dyes BG Rhodamine Green (BG505) and CP tetra-methylrhodamine (CP-TMR) is in the range of enhanced green fluorescent protein (EGFP) and monomeric red fluorescent protein (mRFP), and that BG diethylaminomethyl coumarin (BGDEAC), a derivative of coumarin, is even more stable than enhanced cyan fluorescent protein (ECFP). Due to the increasing number of new BG derivatives with interesting fluorescence properties, such as far-red emission, fluorescence labeling of AGT fusion proteins is becoming a versatile alternative to existing live cell imaging approaches.